A study on blast and fragment resistance of composite metal foams through experimental and modeling approaches. (15th June 2018) - Marx, Jacob; Portanova, Marc; Rabiei, Afsaneh
Abstract: Composite metal foam (CMF) is known for its high strength to density ratio and extraordinary energy absorption capabilities. In this study, stainless steel CMF panels are manufactured and tested against high explosive incendiary (HEI) rounds to study their resistance against explosive blast pressure and the resulting fragments. It is shown that the CMF panels were able to stop the imparted fragments of various sizes, with speeds up to 1500 m/s, and absorb the blast energy without cracking or bowing. The experimental findings were verified using IMPETUS Afea Solver and compared to the performance of a conventional aluminum armor. It is observed that despite their similar mass, the depth of penetration of the fragments into the aluminum plate is higher than that of the CMF panel. Significant front petaling and bulging is observed in aluminum plate following impact of the blast and frags. No petaling and minimal bulging is observed in all CMF panels. In addition, CMF panels are far less stressed when compared to the aluminum plate at any interval following the blast. The experimental and analytical results prove that novel CMF material can be the solution for the pressing need for effective light-weight vehicular armors.